The Effectiveness of Online Simulation with GDL and PBL toward Students’ Digital Literacy Skill - Riki Perdana; Riwayani Riwayani; Jumadi Jumadi; Dadan Rosana (Universitas Negeri Makassar, 2019)
This study aimed to investigate the impact of online simulation in physics learning toward students’ digital literacy skills. There are 106 randomly students Grade XII Science from West Borneo and Riau Province, Indonesia as participants in this study. The level of digital literacy skill of all participants in the classes before and after the learning process was determined to assess the effectiveness of two models with online simulation learning. We used comparative –descriptive, pre-test and post-test experimental design, and Anova Mixed Design to analysis data. The result of this study was: (1) Students’ digital literacy skill of students in two groups initially are at very low level and increased after learning; (2) there was a significant difference in the level of digital literacy skill of the students online simulation with GDL class; (3) in this study, the online simulation with GDL model is more effective than online simulation with PBL model in enhancing students’ digital literacy skill in senior high school. For the conclusion, in this study students’ digital literacy skill in Indonesia is rather below. Model PBL with online simulation is one of the teaching models that can be used in enhancing students’ digital literacy skills.